Iron deficiency in heart failure. Issue 12 (December 2018) - Dinatolo, Elisabetta; Dasseni, Nicolò; Metra, Marco; Lombardi, Carlo; von Haehling, Stephan
Abstract : N/A: Due to aging of the patients with heart failure, comorbidities are an emerging problem and, among them, iron deficiency is an important therapeutic target, independently of concomitant hemoglobin level. Iron deficiency affects up to 50% of heart failure patients, and it has been largely established its association with poor quality of life, impaired exercise tolerance and higher mortality. Randomized controlled trials (RCTs) and meta-analyses have demonstrated that intravenous iron supplementation in heart failure patients with iron deficiency positively affects symptoms, quality of life, exercise tolerance (as measured by VO2 peak and 6MWT), with a global trend to reduction of hospitalization rates. Current European Society of Cardiology Guidelines for heart failure recommend a diagnostic work-up for iron deficiency in all heart failure patients and intravenous iron supplementation with ferric carboxymaltose for symptomatic patients with iron deficiency, defined by ferritin level less than 100 μg/l or by ferritin 100–300 μg/l with TSAT less than 20%. On-going studies will provide new evidence for a better treatment of this important comorbidity of heart failure patients.